Pengaruh Pengetahuan Dan Kualitas PelayananTerhadap Keputusan Menjadi Nasabah Perbankan Syariah - Firmansyah, Arief Firdy (Universitas Negeri Surabaya, 2019)
The purpose of the study is in to increase the knowledge of islamic banking and it’s service quality to public society. The better the service and wide sprodingly the informations about islamic banking system, it could lead into higher chance for people to use “Bank Syariah” The purpose of this research is to know this customers knowledge on islamc banking system and service quality influencing customers for applying islamic banking. Type of the research is quantitative. The result from this study shows that H1 is accepted and H0 is rejected, this customers knowledge on islamc banking system (X1) and service quality (X2) influencing customers for applying islamic banking system in Bank BNI Syariah KC Surabaya. It is also obtained that customer’s value of cofficients and service quality is 55,1% while the rest of the result which is at 44.9% offected by other variables that’s bot being examined on this study.